1980
DOI: 10.1080/10862968009547350
|View full text |Cite
|
Sign up to set email alerts
|

Two Letter Discrimination Sequences: High-Confusion-Alternatives First versus Low-Confusion-Alternatives First

Abstract: Abstract. The procedure of sequencing visual discriminations (the letters b, d, p, and q) in an easy to difficult progression was investigated. In a low-confusion-alternatives first sequence only one choice in an inital match-to-sample task was similar to the target letter. In a high-confusion-alternatives first sequence all the choices in the initial task were similar to the target letter. Twenty preschoolers were randomly assigned to either a lowconfusion-alternatives first or a high-confusion-alternatives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 15 publications
(12 reference statements)
1
10
0
Order By: Relevance
“…While this learning problem has sometimes been attributed to a lack of cerebral dominance (Zangwill 1962), physiological weaknesses (Krise 1952), poor intersensory integration (Birch & Belmont 1964), or emotional disturbance (Blanchard 1935), educators are becoming increasingly interested in instructional solutions; how teachers can present letter-sound correspondences to minimize learner confusion and frustration. Potential instructional solutions include prompting (Hyman & Cohen 1975;Oliver, May, & Downing 1973;Egeland & Winer 1974;Allington 1974Allington -1975, sequencing (Samuels 1973;Nelson & Wein 1974;Carnine 1976;Carnine 1980), and using simultaneous vs successive presentations (Samuels 1969;Williams & Ackerman 1971). The present study grows out of a finding from Carnine's sequencing study (1976).…”
supporting
confidence: 63%
“…While this learning problem has sometimes been attributed to a lack of cerebral dominance (Zangwill 1962), physiological weaknesses (Krise 1952), poor intersensory integration (Birch & Belmont 1964), or emotional disturbance (Blanchard 1935), educators are becoming increasingly interested in instructional solutions; how teachers can present letter-sound correspondences to minimize learner confusion and frustration. Potential instructional solutions include prompting (Hyman & Cohen 1975;Oliver, May, & Downing 1973;Egeland & Winer 1974;Allington 1974Allington -1975, sequencing (Samuels 1973;Nelson & Wein 1974;Carnine 1976;Carnine 1980), and using simultaneous vs successive presentations (Samuels 1969;Williams & Ackerman 1971). The present study grows out of a finding from Carnine's sequencing study (1976).…”
supporting
confidence: 63%
“…algorithm confusion. In another study, Carnine (1980a) found that it was important to separate confusing elements and terminology when teaching new concepts. Moreover, he found that a wide range of examples should be used when teaching new concepts, otherwise students form misconceptions and emit mathematical errors (Carnine, 1980b).…”
Section: Using Computers To Teach Mathematics To Students With Ldmentioning
confidence: 95%
“…The study indicated that students learned letter-sound correspondences more effectively when new learning was introduced after a student was very firm on current and previously taught skills and knowledge in comparison with the rapid introduction of new items. A subsequent study (Carnine, 1980) focused on the introduction of letters that are similar visually, finding that students needed significantly more trials to reach criterion when letters that are visually similar are 178…”
Section: Making Instruction Explicit and Systematicmentioning
confidence: 98%